2014
DOI: 10.1016/j.mod.2013.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Sip1 leads to migration defects and retention of ectodermal markers during lens development

Abstract: SIP1 encodes a DNA-binding transcription factor that regulates multiple developmental processes, as highlighted by the pleiotropic defects observed in Mowat-Wilson Syndrome, which results from mutations in this gene. Further, in adults, dysregulated SIP1 expression has been implicated in both cancer and fibrotic diseases, where it functionally links TGFβ signaling to the loss of epithelial cell characteristics and gene expression. In the ocular lens, an epithelial tissue important for vision, Sip1 is co-expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 75 publications
(115 reference statements)
2
68
0
Order By: Relevance
“…It has been shown that enriched expression in developing lens tissue can be used as a criterion to evaluate potential function in lens development (Lachke et al 2011, 2012a, b; Anand and Lachke 2016; Anand et al 2015; Agrawal et al 2015; Kasaikina et al 2011; Wolf et al 2013; Manthey et al 2014; Dash et al 2015; Audette et al 2016). Consistent with those data, we find that all six candidates are significantly expressed in mouse lens development, and five exhibit lens-enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that enriched expression in developing lens tissue can be used as a criterion to evaluate potential function in lens development (Lachke et al 2011, 2012a, b; Anand and Lachke 2016; Anand et al 2015; Agrawal et al 2015; Kasaikina et al 2011; Wolf et al 2013; Manthey et al 2014; Dash et al 2015; Audette et al 2016). Consistent with those data, we find that all six candidates are significantly expressed in mouse lens development, and five exhibit lens-enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the β1-integrin cKO phenotype is influenced by the concomitant downregulation of β5- and β8-integrin expression in these lenses. However, removal of αV-integrin from the developing lens (which is the obligate α-integrin partner for both β5 and β8-integrin) did not result in lens fiber cell structural defects (Mamuya, Wang, 2014) while β1-integrin was found to be the most abundant β-integrin message detected in the E15.5 embryonic mouse lens by RNA-seq (Manthey et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Mice were genotyped for the Prox1 flox allele and MLR10Cre as described in Table S1. Histology was performed as described previously (Manthey et al, 2014a). No lens defects were observed in mice homozygous or heterozygous for either the MLR10Cre transgene or the Prox1 flox allele alone.…”
Section: Animalsmentioning
confidence: 99%